2001
DOI: 10.2134/agronj2001.931196x
|View full text |Cite
|
Sign up to set email alerts
|

Water Deficit–Induced Senescence and Its Relationship to the Remobilization of Pre‐Stored Carbon in Wheat during Grain Filling

Abstract: nescence promotes remobilization of assimilates are rather obscure. Very little is known about the relation-Remobilization and transfer of the pre-stored food in vegetative ship between these two processes, a surprisingly netissues to the grains in monocarpic plants require the initiation of glected aspect given its importance to yield formation. whole plant senescence. However, mechanisms by which plant senescence promotes remobilization of assimilates are rather obscure. This

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
153
0
2

Year Published

2001
2001
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 252 publications
(175 citation statements)
references
References 52 publications
13
153
0
2
Order By: Relevance
“…Third, the WD imposed in our experiments was rather mild and controlled properly such that plants could rehydrate overnight. We have observed that such a mild WD imposed during grain filling would not seriously reduce photosynthesis (Yang et al, 2000(Yang et al, , 2001a. Under such conditions, the gain from the accelerated grain-filling rate may outweigh the possible loss of photosynthesis as a result of a shortened grain-filling period, leading to an increase in grain yield in the cases where plant senescence is unfavorably delayed by excessive application of N fertilizer.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Third, the WD imposed in our experiments was rather mild and controlled properly such that plants could rehydrate overnight. We have observed that such a mild WD imposed during grain filling would not seriously reduce photosynthesis (Yang et al, 2000(Yang et al, , 2001a. Under such conditions, the gain from the accelerated grain-filling rate may outweigh the possible loss of photosynthesis as a result of a shortened grain-filling period, leading to an increase in grain yield in the cases where plant senescence is unfavorably delayed by excessive application of N fertilizer.…”
Section: Discussionmentioning
confidence: 96%
“…Our earlier work has shown that an increased grainfilling rate is closely associated with an enhanced ABA level in water-stressed grains (Yang et al, 2001a(Yang et al, , 2001c. Here in this experiment, the change in ABA content in the grains and its possible role in the regulation of the enzymatic activities were also investigated.…”
mentioning
confidence: 93%
“…The level of starch in the grain is primarily dependent on photosynthesis occurring in the flag leaf after anthesis, the duration of grain filling, and remobilization from other parts of the plant (Hay and Walker 1989). If environmental conditions are poor during grain filling, then the amount of photoassimilate available for grain filling might be lower, more stored carbon would need to be remobilized, and kernels could be lighter (Yang et al 2001). In the amended plots, the higher weed competition (Beavers 2005) may have reduced the light and other resources available to the wheat plants.…”
Section: á1mentioning
confidence: 99%
“…heavy use of nitrogen (N) fertilizer (Ling et al, 1993;Yang et al, 1996), or adoption of lodging-resistant cultivars of which some stay "green" for too long (Yuan, 1997;Zhu et al, 1997). Our early work showed that water stress imposed during the grain filling of wheat could enhance remobilization of prestored carbon reserves to the grains and grain filling rate (Yang et al, 2000b(Yang et al, , 2001). However, little is known about whether and how plant hormones are involved in the processes.…”
mentioning
confidence: 99%